THE IMPLEMENTATION OF NOTE-TAKING STRATEGY IN LISTENING CLASS - Arianto, Puput (English Education: Jurnal Tadris Bahasa Inggris, 2018)
Note Taking is a skill that helps students to manage the information content of a study. This research aimed at describing the implementation and the roles of note taking in listening class. The method of this research was descriptive qualitative research. The participants consisted of 35 undergraduate students of second semester in English Department of IAIN Surakarta in the academic year of 2017/2018. The result of the research revealed four major findings, they were: 1) In implementing note taking strategy, lecturer played four steps. 2) Note taking had many positive roles such as: a) helps student to get clear main idea, b) differenciate various ideas,c) earn complete ideas, d) make effective recall and review, and e) the structure allows for the easy addition of new information without scratching out or squeezing in. 3) It also had problems among students. This appeared problem caused by students’ lack of vocabulary and lack of advance listening experience. 4) Lecturer was succeed to manage and solve this problem by doing some activities, such as; a) provided background knowledge for student, b) re-played the sudio, c) contexting the new term, and d) used diagram, symbol and abbreviation.Keywords: Note-Taking, Strategy, Listening